Suicides among Medical Students: A Rising Concern - N D Sanjay Kumar (Perspectives In Medical Research)
The trend of increasing incidents of suicides in general and among medical students in parƟcular is a very disturbing trend, which we are witnessing currently and needs immediate aƩenƟon. Medical students are placed in a special situaƟon where they have to deal with lot of pressures simultaneously, like academic pressure, financial pressures (funding their educaƟon), long working hours without breaks, exposure to human suffering, and the false belief that they will be taken less seriously if they seek help. The present editorial would like to throw light on factors which are contribuƟng to suicides among medical students, looking at the systemic lacunae which are perpetuaƟng this crisis and give some acƟonable strategies which will go a long way in reducing the suicides among medical students.